Comparison of human cytochrome P450 1A1-catalysed oxidation of benzo[a]pyrene in prokaryotic and eukaryotic expression systems - Stiborová, Marie; Indra, Radek; Moserová, Michaela; Bořek-Dohalská, Lucie; Hodek, Petr; Frei, Eva; Kopka, Klaus; Schmeiser, Heinz H; Arlt, Volker M (Monatshefte fur chemie, 2017)
ABSTRACT: Cytochrome P450 (CYP) 1A1 is the most important enzyme activating and detoxifying the human carcinogen benzo[a]pyrene (BaP). In the previous studies, we had shown that not only the canonic NADPH:CYP oxidoreductase (POR) can act as electron donor but also cytochrome b5 and its reductase, NADH:cytochrome b5 reductase. Here, we studied the role of the expression system used on the metabolites generated and the levels of DNA adducts formed by activated BaP. We used an eukaryotic and a prokaryotic cellular system (Supersomes, microsomes isolated from insect cells, and Bactosomes, a membrane fraction of Escherichia coli, each transfected with cDNA of human CYP1A1 and POR). These were reconstituted with cytochrome b5 with and without NADH:cytochrome b5 reductase. We evaluated the effectiveness of each cofactor, NADPH and NADH, to mediate BaP metabolism. We found that both systems differ in catalysing the reactions activating and detoxifying BaP. Two BaP-derived DNA adducts were generated by the CYP1A1-Supersomes, both in the presence of NADPH and NADH, whereas NADPH but not NADH was able to support this reaction in the CYP1A1-Bactosomes. Seven BaP metabolites were found in Supersomes with NADPH or NADH, whereas NADPH but not NADH was able to generate five BaP metabolites in Bactosomes. Our study demonstrates different catalytic efficiencies of CYP1A1 expressed in prokaryotic and eukaryotic cells in BaP bioactivation indicating some limitations in the use of E. coli cells for such studies.
Keywords: Coenzymes; DNA; Membranes; Proteins; Enzymes